FILSAFAT ILMU DAN AGAMA (Pengetahuan, Fungsi, Perbedaan dan Persamaan) - Bakir, Moh.; Zayyadi, Ach. (SAMAWAT: Journal Of Hadith and Qur’anic Studies, 2018)
Science, philosophy and religion are the three components that direct human beings in achieving the goal of life. In historical conjunctions, human science from time to time continues to change and develop. Philosophy together with art, belief and science form human existence, as a system that interacts with each other. Religion becomes the grip and manhaj of mankind. Science, Philosophy and religion have different fields and objects, but they all make a great contribution to human life. Keywords: Philosophy, Religion, Man